STUDENTS' PERCEPTIONS TOWARD TEST OF ENGLISH FOR ACADEMIC PROFICIENCY (TEAP) AS A REQUIREMENT FOR THESIS EXAMINATION: A Case Study at Non-English Study Program of IKIP PGRI Pontianak - Neovania Yutsentak; Abdul Arif; Citra Kusumaningsih (Journal of English Language Teaching and Education (JELTE), 2024)
TEAP has been used as a part of requirement in various aspects of tertiary education, including as a part of the requirement for undertaking thesis examinations both for English and non-English study program students. However, there appears few studies investigating the students’ perceptions toward TEAP as a requirement for thesis examination. This study qualitative case study aims to know non-English students’ perception toward TEAP as one of the requirements for thesis examination as well as to know the challenges and difficulties they experience in taking TEAP. The study involves 11 non-English students of IKIP PGRI Pontianak who were selected using purposive sampling. The data were gathered through interviews and documents. The data were analyzed using thematic analysis. The research finding shows that TEAP is perceived to be an assessment for learning and a hinder to finish the study timely. The findings also show that, as a requirement for thesis examination was perceived to be useful for assessing students’ English academic proficiency and motivating them to improve their English academic skills. The research findings also show that the challenges and difficulties experienced by the students are lack of understanding TEAP system, lack of training, and hard to achieve the minimum TEAP score. This research highlights the usefulness of TEAP for non-English language students, the importance of considering and anticipating the challenges, and difficulties of taking TEAP, and the importance of preparing and offering sufficient training of TEAP and English courses.